Análise dos fatores relacionados do diagnóstico de enfermagem desobstrução ineficaz de vias aéreas em crianças com doença respiratória - Andrade, Lívia Zulmyra Cintra (2018)
The identification of the associations between factors that refer to the diagnosis and to the nursing diagnosis is fundamental for the understanding of the causal process that is established. The knowledge of the factors that are linked to the appearance of the diagnosis or the potential or effect of a causal factor can aid the diagnostic and therapeutic reasoning and is the starting point for the implantation of curative and preventive measures. The objective was to analyze the related factors to the nursing diagnosis. Ineffective airway clearance in children with respiratory disease. It is a case-control study, carried out in an inpatient unit of two children's hospitals in the city of Fortaleza-Ceará, from August 2016 to July 2017. We evaluated 400 children aged 0 to 5 years, pneumonia and/or asthma. For a data collection, perform a lung assessment and interview with the components. Subsequently, the data were organized and analyzed by the researcher to determine the presence or absence of the defining characteristics and related factors of Ineffective airway clearance, based on previously established research protocols. The determination of the diagnosis and the classification of the groups of cases and controls occurred through the statistical analysis of latent class models. The related factors to the launching of tests for predisposition, incapacitation, precipitation and reinforcement. For statistical analysis, we used the IBM SPSS software and the statistical package R, and adopted a significance level of 5%. The study was approved by the Research Ethics Committee. The majority of the male children (56.0%), with an average age of 20 months. The most frequent respiratory diseases were pneumonia (84.0%) and asthma (28.8%). From the latent class model, 90.25% of the children showed a nursing diagnosis. As defining characteristics adventitious breath sounds, excessive sputum, ineffective cough and dyspnea presented high prevalence and sensitivity. Ineffective airway clearance in children with respiratory disease is an association for defined characteristics. Related factors to infection (93.8%), retained secretions (91.0%), excessive mucus (84.8%), exposure to smoke (65.8%) was more prevalent. Allergic airway, airway spasm, exudate in the alveoli, excessive mucus, and retained secretions are more likely to identify the clinical outcome. Retained secretions followed by excessive mucus are the factors related to the greatest impact on the occurrence of Ineffective airway clearance in the studied population. Infection, allergic airway and exposure to smoke act as precipitating factors. Meanwhile, airway spasm, exudate in the alveoli, retained secretions and excessive mucus are reinforcing factors in the process of diagnostic causation of nursing. As the clinical evidence obtained highlights important contributions to nursing knowledge and practice aimed at children with respiratory diseases. A clearer understanding of the processes of interaction between causal factors and clinical indicators for the manifestation of the human response can contribute to support the diagnostic reasoning, select more focused nursing interventions and subsidize better quality nursing care.